[PP.38.08] SLOW LOADED BREATHING TRAINING ATTENUATES THE EXERCISE PRESSOR RESPONSES IN THE ELDERLY WITH ISOLATED SYSTOLIC HYPERTENSION. (September 2016) - Sangthong, B.; Jones, D.; Jones, C.
Abstract : Objective: Metaboreflex sensitivity is enhanced in hypertensive patients and slow breathing training lowers blood pressure (BP) responses to static handgrip exercise in essential hypertension. Isolated systolic hypertension (ISH), which affects more than 80% of older people, has a different pathology and it is not known whether slow breathing can reduce the metaboreflex in these patients. This study aims to determine the effect of slow loaded (LB) and unloaded breathing (ULB) training on the BP responses to handgrip exercise in patients with ISH. Design and method: Thirty older ISH patients (67 ± 5 yrs) were randomized into LB, ULB and Control (C) groups. LB and ULB trained for 8 weeks with inspiratory loads of 18 cm H2O or no load. All patients performed 2 minutes static handgrip exercise (30% MVC) followed by 2 minutes post exercise circulatory occlusion (PECO) before and after the breathing training period. Results: The pre-training sBP responses to handgrip were increases of 44 and 42 mmHg in LB and ULB, which were reduced by 12.6 mmHg in LB and 7.2 mmHg in ULB, the difference between groups being significant (p = 0.037). Only LB showed a reduction in sBP during PECO (9.5 mmHg, p = 0.01), indicating that loaded breathing reduced metaboreflex sensitivity in these patients. Conclusions: While ULB and LB both reduced sBP during handgrip exercise, only LB reduced sBP during PECO. This suggests that ISH patients have at least two pathologies, one that is improved by slow breathing (both LB and ULB) together with an increased metaboreflex sensitivity, which is only reduced by an inspiratory load.